The Relationship Of Rewarding With Work Motivation Of Honorary Nurses - Nadia Alfira; Safruddin (Comprehensive Health Care, 2017)
Nursing as a science that continues to develop, both due to external pressure and because of internal pressure nursing. One of the problems faced by Indonesian nurses in the health service system is the low standard of reward which can have an impact on nurse performance. The purpose of this study was to determine the relationship of rewarding with work motivation of nurses in the Inpatient Room of H. Andi Sulthan Daeng Radja Hospital in Bulukumba Regency, with total sampling taking 48 respondents.This research is a quantitative study using an analytic observational design using a cross-sectional study approach. The results of bivariate fisher analysis showed that the value of the p-value was 0.028 p (<0.05). The value of 0.028 is below the alpha value (0.05), thus there is a relationship between giving rewards with work motivation of nurses.Then it was concluded that there was a relationship between rewarding and work motivation for honorary nurses in the inpatient room of H. Andi Sulthan Daeng Radja Hospital in Bulukumba Regency. Based on the results of the study it is expected to the Hospital to provide more appropriate rewards or awards to improve better nursing services.